Mimetic Neural Networks: A Unified Framework for Protein Design and Folding - Eliasof, Moshe; Boesen , Tue; Haber , Eldad; Keasar , Chen; Treister , Eran (Frontiers in Bioinformatics, 2022)
Recent advancements in machine learning techniques for protein structure prediction motivate3 better results in its inverse problem – protein design. In this work we introduce a new graph4 mimetic neural network, MimNet, and show that it is possible to build a reversible architecture5 that solves the structure and design problems in tandem, allowing to improve protein backbone6 design when the structure is better estimated. We use the ProteinNet data set and show that the7 state of the art results in protein design can be met and even improved, given recent architectures8 for protein folding.